Polscy księża zesłańcy postyczniowi o Rosji - Cybulski, Marcin (Acta Polono-Ruthenica, 2018)
The given article is devoted to the problem of the perception of Russia and the Russians in Polish Catholic priests’ literary work, exiled after the January Uprising to the Russian Empire. As commonly assessed, exile to Russia affected about six hundred Polish clergymen, in one way or another connected to the insurrectionary move of 1863. The most famous priest-exiles, whose literary legacy has survived to this day, are: Mikołaj Kulaszyński, Stanisław Matraś, Edward Nowakowski and Zygmunt Szczęsny Feliński. A present article was devoted to it is for these writers, and is concentrating on the stereotype of the Russians and Russia. The text includes the following aspects one by one: national nomenclature, psychological and characterological features, physical properties of the Russians and the general image of Russia as the state and the country.